Effect of multiple feedings in the operation of a high-pressure polymerization reactor for ethylene polymerization - Asteasuain, Mariano (2006)
A thorough model of the high pressure polymerization of ethylene in tubular reactors previously developed by the authors is used to analyze operating conditions for a specific industrial reactor. The objective is to maximize productivity while keeping product quality within desired parameters. The variables under analysis are: position, rate and temperature of lateral reactor feeds, reactor jacket configuration, temperature and flow rate of the refrigerant. Separating the initiator injections provides an increase in conversion, but also in polydispersity. However, this undesirable effect in polydispersity can be sorted out by manipulating the modifier flow rate properly. Besides, the refrigerating cost can be significantly reduced by means of a proper jacket configuration and an optimized refrigerant flow rate. In this way we show the usefulness of the mathematical model as a predictive tool -in comparison with pilot or industrial scale trials- especially when processes are carried out under severe operating conditions.